Collaborative learning a process in the interaction in learning environments of children of 3 years - Contreras Chariguamán, Sandy; Noboa Torres, María; Lucio Quintana, Araceli (Revista Universidad de Guayaquil, 2017)
Collaborative learning is one of the learning methodologies that, despite having been established for several centuries, now again begins to have the importance of the case within the classroom. However, despite its rise and the various studies that validate its benefits, in reality there is very little that is known regarding how it can be developed within the classroom and what elements it considers for the respective implementation. In this context, the aim of this manuscript is to provide the reader with a document that focuses on collaborative learning as a process of interaction in the learning environments of 3-year-old children from a theoretical perspective in the first instance and after this, through the application of the instrument chosen to identify the behavior of the infant and its behavior in the teaching center, the instrument applied was the inventory of children’s behavior CBCL (Child Behavior Checklist) to a total population of 19 children, without However, those who answered this test were the parents of each one of them. As main findings, it was found that the items that presented the greatest inconvenience during the evaluation were (can not remain seated or are very restless, can not wait, wants everything at the moment, destroys the things of their family or other children, easily frustrated) whose rating was 2, that is, according to the test’s rating parameter was "almost always".